Updates on Dengue Vaccine and Antiviral: Where Are We Heading? - Harun Norshidah; Ramachandran Vignesh; Ngit Shin Lai (Molecules, 2021)
Approximately 100–400 million people from more than 100 countries in the tropical and subtropical world are affected by dengue infections. Recent scientific breakthroughs have brought new insights into novel strategies for the production of dengue antivirals and vaccines. The search for specific dengue inhibitors is expanding, and the mechanisms for evaluating the efficacy of novel drugs are currently established, allowing for expedited translation into human trials. Furthermore, in the aftermath of the only FDA-approved vaccine, Dengvaxia, a safer and more effective dengue vaccine candidate is making its way through the clinical trials. Until an effective antiviral therapy and licensed vaccine are available, disease monitoring and vector population control will be the mainstays of dengue prevention. In this article, we highlighted recent advances made in the perspectives of efforts made recently, in dengue vaccine development and dengue antiviral drug.